Sinergitas Pemenuhan Kebutuhan Informasi Melalui Program Paperbuk di Perpustakaan Unisa Yogyakarta - Zeni Istiqomah; Layyina, Lilik; Rachmawati, Dita (Perpustakaan Universitas Gadjah Mada, 2024)
The library and its patrons synergize to fulfill their respective functions and roles. At the forefront of information provision, the library has the task of providing information tailored to the needs of its patrons. This research aims to analyze the synergy the Unisa Yogyakarta Library conducted in meeting information needs through the